Molecular Detection of Ricketssia africae and Candidatus Midichloria mitochondrii in Cattle Ticks from Cameroon - Mbafor, Fidelia Lem; Osei-Mensah, Jubin; Kwarteng, Sandra Abankwa; Addo, Seth Ofei; Manchang Tanyi Kingsley; Michael E. DeWitt; Patrick Kwasi Obuam; Ewurabena Oduma Duker; Jessica Dufie Boakye; Gayheart Deladem Agbotse; Folitse, Raphael Deladem; Achille Paguem; Emikpe, Benjamin Obukowho (Faculty of Veterinary Medicine Universitas Brawijaya, 2025)
Ticks spread pathogens that affect both human and animal health and often cause significant economic losses to the livestock industry. However, there is limited data on the distribution of ticks and tick-borne pathogens, particularly those affecting cattle in Cameroon. In this study, ticks were collected from cattle in Buea, the capital of the South West Region of Cameroon, to determine their diversity and identify tick-borne pathogens through PCR and sequencing. The tick samples were screened for pathogens using assays that target the rOmpA gene (ompA) of Rickettsia, the ssrRNA gene of Babesia and Theileria and the Ehrlichia genus 16SrRNA gene. A total of 458 ticks were collected with Rhipicephalus annulatus (65.6%) as the predominant species. From 68 tick pools screened, 26 (38.2%) were positive for pathogen/ symbiont DNA. The pathogen identified was Rickettsia africae (22.1%). This study reports the first molecular detection of the symbiont Candidatus Midichloria mitochondrii (22.1%) in the sampled tick species. It was observed that male ticks were significantly more likely to test positive for R. africae (OR = 208, 95% CI = 28.6 - 4553, p<0.001). Animal handlers may face the risk of these zoonotic infections and as such, there is a need to employ protective measures to prevent or reduce pathogen spread.